Preparation and properties of phosphate starches from tuberous roots - Leonel, Magali [UNESP]; Del Bem, Marília S. [UNESP]; dos Santos, Thaís P.R. [UNESP]; Franco, Célia Maria Landi [UNESP] (Elsevier, 2021)
The diversification of raw materials in the starch industries is a current strategy. However, the production of native starches does not meet market demand, and it is essential to expand the knowledge about chemical modifications in the same production line for different sources of starch. Phosphate starches are one of the most abundantly produced and widely used chemically modified starches. However, the effects of this modification may vary with the starch source and the reaction conditions. In this study, arrowroot, cassava and sweet potato starches were modified with sodium trimetaphosphate (STMP)/sodium tripolyphosphate (STPP) mixture under same conditions. The reaction time ranged from 7.5 to 120 min. Unmodified and modified starches were analyzed for phosphorus, amylose, morphology, X-ray diffraction pattern, crystallinity, swelling power, solubility, pasting and thermal properties. Phosphorus content linked to the starches increased with the reaction time, which affected the physicochemical properties of the three starches. The changes were more significant in all reaction times for cassava starch, followed by arrowroot. Due to its intrinsic characteristics, longer reaction times were necessary for more significant changes in sweet potato starch. Regardless of the starch source, as the reaction time increased, the average starch granule diameter, swelling power, solubility and peak viscosity increased. There was a decrease in setback in the longer reaction times for cassava and arrowroot starches. The changes in the reaction times allowed obtaining phosphate tuberous starches with different properties which can meet the demands of the food and non-food industries.
Keywords: Arrowroot; Cassava; Sweet potato